Hubungan Antara Self Efficacy dan Regulasi Emosi dengan Resiliensi pada Remaja yang Tinggal di Panti Asuhan - Laura, Septia; Ulfah, Khoiriya (ANFUSINA: Journal of Psychology, 2020)
Resilience is the ability of a person or individual to rise from the problems being faced. Resilience is very important to be owned by every individual because if an individual does not have resilience, then the individual will be difficult to rise from adversity due to the problems faced. This study aims to determine the relationship between self efficacy and emotion regulation with resilience in 58 adolescents living in Mahmudah orphanage in Bandar Lampung. The sampling technique used is total sampling and then analyzed using multiple regression analysis techniques. The results of the analysis of this study indicate that there is a relationship between self efficacy and emotion regulation with resilience in adolescents living in orphanages with correlation coefficients R = 0.645 and F = 19.634 with p = 0,000. Then, there is a relationship between self efficacy with resilience in adolescents living in orphanages, the results of the analysis obtained are the value of rx1y = 0.373 with p = 0,000. Furthermore, there is a relationship between emotional regulation with resilience in teens living in orphanages, the results of the analysis obtained are the value of rx2y = 0.601 with a value of p = 0.002.